CHARACTERIZATION OF BAMBOO TUTUL CHARCOAL PARTICLE PRODUCED BY HIGH ENERGY BALL MILLING SHAKER TYPE - Supriyono, S; Susilo, B. (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2019)
The objective of this study is to characterize bamboo tutul charcoal particles produced by High Energy Ball Milling (HBEM) shaker type. The HEBM process was conducted in the stainless steel vials for 2 million cycles at 900 motor RPM. The ball milling diameter was 1/4 inch made from steel. Therefore, perhaps the final particle size will be determined by empty space of the vial for the movement of the balls. In this study, the empty space is varied for 1/2, 1/3, 1/4, and 1/5 of vial volume. Particle Size Analyzer (PSA) is used to have the particle sizes and SEM-EDX is used to have surface morphology of the particle. The average final particle sizes are 547.8 nm, 522.9 nm, 422.7 nm, and 739.4 nm for 1/2, 1/3, 1/4, and 1/5 empty space of vial respectively. The surface morphologies of the particles are determined by fracture mechanism as they can be seen on the SEM results. Based on the results, it can be said that there is no correlation between the particle size and the empty space of the vial. As long as there is space for movement of the milling balls, the collision occurs and the reduction of the particle also happens.